Crusading on the Edge - Nielsen, Torben Kjersgaard; Fonnesberg-Schmidt, Iben (Brepols, 2016)
This volume brings together contributions from fifteen historians and art historians working on the history of the crusades, focusing on Iberia and the Baltic region. The subjects treated include the historiography of the Iberian and Baltic crusades; the transfer of crusading ideas from the Holy Land to Iberia and the Baltic region and the use of such ideas in local rhetoric and propaganda; the papal attitudes towards the Iberian and Baltic campaigns; the papal attitudes towards Muslims living in Christian Spain; the interaction between conquered and conquerors as reflected in art and architecture; and the exchange of information about the crusades in Iberia and the wider Baltic Region. The collection thus throws further light not only onto events in the Iberian Peninsula and the Baltic region but also onto the development of the crusade movement in general. It constitutes a valuable resource for both undergraduates and postgraduates studying the crusade movement in the Middle Ages. <span class=